Continuity of Care for Post-Coronary Artery Bypass Grafting (CABG) Patients: A Literature Review - Qodri Alamsyah; Wan Nishfa Dewi; Erika Erika (GLOBAL HEALTH SCIENCE GROUP, 2026)
Post-CABG period is often characterized by medical complications, functional limitations, psychosocial problems, and a high risk of readmission. This review aims to examine the scientific evidence related to continuity of care in post-CABG patients, including the effectiveness of nursing interventions and cardiac rehabilitation in influencing patient outcomes. The method used was a literature review with a narrative approach, through searches of articles in PubMed, Scopus, ScienceDirect, and Google Scholar (2019–2025). Of the 1,863 articles initially identified, 9 met the inclusion criteria and were analyzed thematically. The results show that systematic nursing interventions such as discharge planning significantly reduce readmissions and medical complications, as well as improve quality of life. Home-based, outpatient, and telerehabilitation cardiac rehabilitation programs are effective in improving functional capacity, patient adherence, and productivity. Biopsychosocial support, integration of psychological rehabilitation, and patient participation through shared decision-making enhance coping, satisfaction, and patient engagement. Contextual factors such as geographical location and access to health services also influence outcomes. In conclusion, continuity of care after CABG requires an integrated, multidimensional intervention approach that encompasses physical, psychosocial, and socioeconomic aspects, in order to enhance clinical effectiveness, accelerate recovery, and support patients’ social reintegration.